Residual herbicides increase the period prior to interference in soybean cultivars - Rizzardi,Mauro A. (2020)
Abstract Background: The pre-emergence herbicides diclosulam and flumioxazin are used to weed control in soybean. We hypothesized management of the new emergence of weeds in the early development stages of the soybean could alter the periods of interference. Thus, the period prior to interference allows and increases the canopy closure spaces before the critical period and disfavors the development of weeds inside the vegetative canopy. Objective: This study aimed to evaluate whether the period prior to interference of soybean cultivars was altered due to the application of residual pre-emergence herbicides. Methods: Two experiments were conducted with the soybean cultivars ‘NA 5909 RG’ and ‘P95R51’. One day before sowing in the main plots, the herbicide treatments paraquat (control without residual herbicide), paraquat+diclosulam, and paraquat+flumioxazin were applied. In the sub-plots, the increasing periods of coexistence of soybean with weeds of 0, 7, 14, 21, 28, 35, 42, and 49 days after the emergence of soybean were allocated. Results: The control without residual herbicide had the lowest period prior to interference and the most considerable reductions in grain yield when compared with residual herbicides in both experiments. The presence of residual herbicide increased the period prior to interference because they controlled the initial emergence of the major weeds in the experimental area. Conclusions: The use of the herbicides with residual activity diclosulam and flumioxazin increased the period prior to interference of ‘NA 5909 RG’ and ‘P95R51’ in areas infested mainly with horseweed and radish.